ANALISIS PEMAHAMAN KONSEP CALON GURU SEKOLAH DASAR PADA KONSEP PENCERNAAN - Andayani; Rif’at Shafwatul Anam; Monika Handayani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article provides an overview of the understanding of prospective elementary school teachers regarding the digestive concept. The research described in this article is descriptive research with a survey type, which was delivered to 105 elementary school teacher candidates. The instruments distributed were conducted online in the form of multiple choices related to the concept of digestion and a questionnaire related to their learning experiences. Based on the results, it was found that, in general, the answers given by prospective teachers were not in line with expectations. It is proven by the average percentage of correct answers of 45.12%, which was categorized in the